2007
DOI: 10.1148/radiol.2451060530
|View full text |Cite
|
Sign up to set email alerts
|

Large-Vessel Distensibility Measurement with Electrocardiographically Gated Multidetector CT: Phantom Study and Initial Experience

Abstract: The purpose of this study was to prospectively examine vessel distensibility measurements by using electrocardiographically gated multidetector computed tomography (CT) in a phantom compared with measurements by using a digital camera and to examine feasibility in humans. Large-vessel phantoms were constructed, using a pulsatile flow pump, and absolute diameter and percentage diameter changes during pulsation were measured. After institutional review board approval and patient consent were obtained, the abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Zhang et al (2007) measured a cross-sectional area change between 2.97% and 5.46% on the aorta, using an ECG-gated CT, and our value falls within this range. It can be seen in Fig.…”
Section: Solid Domainsupporting
confidence: 55%
“…Zhang et al (2007) measured a cross-sectional area change between 2.97% and 5.46% on the aorta, using an ECG-gated CT, and our value falls within this range. It can be seen in Fig.…”
Section: Solid Domainsupporting
confidence: 55%
“…Therefore, the ability to evaluate aortic elasticity non-invasively early on is of great interest. A previous study had reported that measurement of vessel distensibility by using an electrocardiographicallygated MDCT angiographic protocol was accurate in a phantom [9]. MDCT had recently been used in the distensibility assessment of the abdominal aortic wall and in the conformational change evaluation of the thoracic aorta in patients with chronic aortic dissection type B [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For every cardiac phase a contour of the lumen area was drawn at the same positions along the centerline. Contrary to the studies on the aorta [5,6,7] where the area was calculated using voxel counting, the contours used in this study had subvoxel precision. Calculation of the cross sectional area from the drawn contours then leads to the area curve of the vessel during one heart cycle.…”
Section: Manual Measurementsmentioning
confidence: 96%
“…Assuming a circular crosssection, the area is then calculated. Recently, several studies have demonstrated the feasibility of semi automated measurement of the distensibility of large vessels (aortic arch, abdominal aorta) using ECG-gated CTA [5,6,7]. An advantage of CTA over ultrasound is that the true cross-sectional area can be measured, and thus noncircular cross-sections can be accounted for.…”
Section: Introductionmentioning
confidence: 99%